Psychic Causation in Indonesian Criminal Law: A Normative Study Using A Material Offense Approach - Hadi Purnomo; Kamil Razak; Hana Krisnamurti (Civiliza Publishing, 2026)
This paper examines psychic causality in Iindonesian crimiinal law through normative legal research and a material offence approach. Classical criminal law tends to identify criminal causation through physical acts, such as stabbing, striking, oir poisoining. However, contemporary criimiinal cases increasingly involve non-physical acts, includiing verbal intimidation, psychological pressure, threats, humiliation, coercive communication, and digital harassment, which may allegedly trigger severe psychological harm or even suicide. The central legal question is whether psychological pressure may be legally constructed as a cause of a prohibited result. This paper argues that psychic causality cannot be assessed solely through the conditio sine qua noin theory because such theory is too broad when applied to psychological events. Instead, legal causation requires a coimbination of factual causation, adequate causation, objective foireseeability, and normative attribution. Indonesian law has recognized psychological suffering through several legal instruments, including the Criminal Code, the Domestic Violence Law, the Sexual Violence Crime Law, the Electronic Information and Transactions Law, and the new Criminal Code. Nevertheless, the main difficulty lies not in the existence of norms, but in proving the causal chain between the perpetrator’s conduct and the victim’s psychological condition. Therefore, forensic psychiatric expertise, psychological autopsy, medical records, digital evidence, and witness testimony are crucial to bridge legal certainty and scientific probability.